Endovascular treatment using woven stents for ruptured vertebral artery dissecting aneurysm induced by varicella zoster virus: case report. (1st November 2016) - Lee, Kwangho; Park, Hyun; Park, Insung; Han, Jongwoo
Abstract: Subarachnoid hemorrhage with ruptured cerebral artery dissection caused by varicella zoster (VZ) vasculopathy is rare. We report a rare case of vertebral artery (VA) dissection induced by VZ virus, successfully treated with stent-assisted coil embolization and systemic anti viral medication, on six month follow-up cerebral angiography with the review of literatures.